A low cost paper tissue-based PDMS/SiO2 composite for both high efficient oil absorption and water-in-oil emulsion separation. (20th January 2020) - Sun, Jiawei; Bi, Hengchang; Jia, Haiyang; Su, Shi; Dong, Hui; Xie, Xiao; Sun, Litao
Abstract: The pollution of water resource and shortage of clean water have become increasingly severe, developing an urgent demand of reliable, efficient yet low-cost material for everyday water purification. In the present work, a superhydrophobic paper tissue-based SiO2 /PDMS composite has been prepared for both oil absorption and water-in-oil emulsion separation. The fabrication process is quite simple since it takes the full advantage of tissue that has naturally strong capillary force of which allows the material to absorb oil from water much more rapidly and completely (>99.9%) even under harsh conditions. The study has shown the novel material is exceptionally efficient in separating water-in-oil emulsion under gravity but no need of extraneous pressure. A variety of emulsions has been proven with high flux (>2, 000 L m −2 h −1 ) and high separation efficiency (>99.4%). It is believed that this study has proposed a highly reliable and efficient, low cost strategy in both oil absorption and water purification, which shed light on water treatment of both civil use and industry. Graphical abstract: Image 1 Highlights: The composite prepared by paper tissue makes the cost quite low. The composite takes advantage of strong capillary of paper tissue. The composite can be practicably used for oil absorption and emulsion separation.